KAJIAN KOMPARATIF HISTORIS FILM 'PENGABDI SETAN' - Iktia, Garcia (Jurnal Budaya Nusantara, 2018)
Indonesian films experience development over time. In the beginning film in Indonesia served as a massmobilizer and propaganda, then suspended animation. Now Indonesian films are taken into account to internationalfestivals, especially the horror film genre. The object to be analyzed in this study is a horror film, entitled 'PengabdiSetan' by director Rudi Sudjarwo produced in 2017 which is also nominated for the Indonesian Film Festival. Researchthrough the analysis of historical studies with comparative research methods, literature study of two films that have beenadapted to the same genre, namely the horror genre. Both films have good unity in the story and cinematography, but inthe film Ã¢â‚¬Å“Pengabdi SetanÃ¢â‚¬Â made in 2017 the audience is treated to a different cinematography than the one made in 1980and the many cinematographic developments in the Indonesian film horror genre.